Children Moving Across Borders: Equitable Access to Education for Undocumented Migrants in South Africa - Blessed-Sayah, Sarah Enaan-Maseph (University of the Witwatersrand, Johannesburg, 2023)
South Africa is experiencing an increase in intra-regional migration, and the management of migration in the country is increasingly becoming highly securitised. Individuals who move intra-regionally across borders include children –accompanied by parents or caretakers, unaccompanied, and those seeking refuge because of untenable and oppressive circumstances in their home country. Also, individuals who move to South Africa without legal documentation often give birth to children within the State, who are then undocumented. Without documentation, these children cannot access education, which means that achieving their educational right becomes impossible. This happens partly because of legal contradictions that exist in immigration and education policy frameworks. For instance, the Bill of Rights, as contained in Section 29(1)(a) of the Constitution of South Africa (The Constitution of the Republic of South Africa No. 108, 1996), states that everyone has the right to basic education, and further states in subsection 2 that the State (being South Africa) is obligated to respect this right. Additionally, the South African Schools Act 84 of 1996 (Republic of South Africa, 1996) states that public schools are obliged to admit children without any form of discrimination on any grounds. However, the Immigration Act No 13 of 2002 states that no ‘illegal foreigner’ should be allowed on the premises of any learning institution (Republic of South Africa The Presidency, 2002). Thus, the question remains whether undocumented migrant children are included in the ‘all’ or ‘every’ because of existing legal contradictions between the Constitution and the Immigration Policy. Furthermore, the need to consider how the educational right of undocumented migrant children is upheld comes from the evident nationalist view on migration in South Africa, which is projected through government, and in local communities. Although some studies have evaluated the extent to which this right is protected or ensured, and others have considered the barriers to exercising the right to education in South Africa, only a few specifically focus on the right of undocumented migrant children to equitable education, and strategies to ensure its fulfilment. Thus, an explanation of equitable access to education in South Africa entails developing an approach for understanding undocumented migrant children’s educational experience, because this approach would provide a platform to achieve workable ways to ensure the fulfilment of their right to basic education. This research explores the difficulties undocumented migrant children experience in relation to education. Given this, an explanation regarding access to education for undocumented migrant children, from an equity viewpoint in South Africa, is developed. Thus, this study had three major aims. Firstly, to develop an understanding of equity in relation to access to education. Secondly, to investigate the impact (problems) of migration on undocumented migrant children in relation to equitable access to education in South Africa. Thirdly, to develop strategies that can ensure that these undocumented migrant children have their right to basic education protected in South Africa. Using the capability approach combined with Unterhalter’s (2009) description of equity as a three-fold concept as the study’s conceptual framework, I argue that ensuring equitable access to education for undocumented migrant children in South Africa requires an integrated approach, which goes beyond top-down strategies and highlights the role of agency. Each finding under the study’s objectives serves as evidence that support my overall argument for an integrated approach. A qualitative research design, from an interpretivist phenomenological lens provided me with the opportunity to carefully interact and bring forward the contextualised lived experiences of undocumented migrant children. This brought about an in-depth description of equitable access to education for them. The study was conducted with an NGO working with undocumented migrant children in the eastern region of the Johannesburg area in the Gauteng province of South Africa. The criterion used for selecting participants was based on the fact that the Project staff members, children who attend the Project, and their parents understand the social environment in which the children reside. They were able to give detailed and in-depth explanations on the impact of migration on their access to education, in an equitable manner. Gauteng Department of Education (GDE) officials who deal with undocumented migrant children, and South African Human Rights Commission (SAHRC) staff who deal with education also understand the impact of migration on these children’s chance to equitably access education and were included in the study. A total of 45 participants who were conveniently selected, based on the inclusion criteria, made up the sample size. Nineteen undocumented migrant children (n=19), eleven parents of undocumented migrant children (n=11), and fifteen professionals participated in this study (n=15). I served as the primary tool for data collection while employing different qualitative methods, including individual semi-structured interviews and focus group discussions. The method of data analysis I used for this study included an inductive and deductive approach using the NVivo QSR 12 software. From this method of data analysis, I identified three key themes relating to the specific objectives of the study. Objective 1: I found that undocumented migrant children, their parents, and professionals who deal with this group of children perceive equity to mean ‘the opportunity to thrive’ and ‘fairness’. In addition, under the first objective, it was found that equitable access to education is closely linked to being able to attend schools. While the undocumented migrant children described this in terms of the right to attend school and learn educational skills, the parent and professional participants explained it as a fundamental human right which should not be constrained by one’s legal status in South Africa. Along this line, it was also revealed that equitable access to education is important for various reasons including access to other services; capabilities, functioning, and the platform to achieve other human rights; and the avoidance of social ills. In all, equitable access to education strongly supports the human dignity of undocumented migrant children. Objective 2: Under objective two, I found that the impact of migration to South Africa, as it concerns equitable access to education for undocumented migrant children, was negative. Various problems faced by these children were identified. Firstly, the overarching problem was the lack of documentation which affects the opportunity for undocumented migrant children to equitably access school. This lack of documentation includes the non-issuance of proper birth certificates and so, the non-registration of the births of these children; and the fear of going to renew or apply for permits at the South African Department of Home Affairs (DHA) because of fear of police arrest. Secondly, the problem of continued discrimination, and xenophobic attacks and attitudes was also experienced by undocumented migrant children and their parents. These attacks affected their chance to access education. Thirdly, the lack of access to basic services presented itself as a difficulty which affects the opportunity to access schools, in an equitable way. Fourth, policy gaps, including ambiguities and non-implementation of recent court judgments, also served as problems which affect access to education for these children. Lastly, Covid-19 and the effects of the pandemic further compounded already existing difficulties undocumented migrant children face concerning their equitable access to education. Objective 3: The study revealed that strategies to address the problems experienced by undocumented migrant children include government-level, community-level, and individual-level strategies, and a combined, planned approach (integrated approach). Under government-level strategies, it was found that undocumented migrant children need to be issued birth certificates with identification or registration numbers and so, be appropriately registered at birth. Existing policies about education and immigration also need to be revised, and recent court judgments like the Phakamisa Judgment must be implemented. Also, stakeholders must be trained to ensure the proper implementation, monitoring, and evaluation of policies and recent judgments on equitable access to education for undocumented migrant children. As part of community-level strategies more assistance from NGOs, who bridge educational gaps for undocumented migrant children, would be useful in ensuring undocumented migrant children get educated. Individually, promoting social cohesion between migrants and non-migrants was highlighted. Also, parents of the identified children were encouraged to acquire documentation for their children. However, these different levels, on their own, are not sufficient to ensure equitable access to education. Thus, this study advocates an integrated approach to addressing the problems experienced by undocumented migrant children and their parents, regarding their children’s equitable access to education. Supporting this, the professionals interviewed recommend that all levels of society need to work together, in an organised way, to achieve access to education for the identified group of children. Also, the role of the agency and a bottom-up approach to ensuring access to education in an equitable way were highlighted through the integrated approach. Based on the findings, I argue that the various strategies identified require an integrated approach (for thinking and doing), which includes recognising the agency (individually and collectively) of undocumented migrant children. This approach draws on both top-down and bottom-up approaches with the significant roles of policy implementation, monitoring, and evaluation as well as agency (in both individual and collective forms) highlighted. Important is that this integrated approach (for thinking and doing) will be based on a thorough knowledge of the context. The findings thus serve as supporting empirical evidence for the overall thesis which is that to ensure equitable access to education is achieved, equity must be explained in detail, as a multi-faceted notion, and combined with the capability approach, which allows us to identify and interrogate specific structural limitations.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Humanities, at the Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Undocumented migrant children; Migration; Capability Approach; Equity; Education; Equitable Access; South Africa; UCTD; SDG-4: Quality education